a) [tex]lim=\frac{\sqrt[m]{1+ax}.\sqrt[n]{1+bx}-1}{x}=\frac{\sqrt[m]{1+ax}.\sqrt[n]{1+bx}-\sqrt[m]{1+ax}+\sqrt[m]{1+ax}-1}{x}=\frac{\sqrt[m]{1+ax}bx}{x(1+\sqrt[n]{1+bx}+...+\sqrt[n]{1+bx}^{n-1})}+\frac{ax}{x(1+\sqrt[m]{1+ax}+...+\sqrt[m]{1+ax}^{m-1})}=\frac{b}{n}+\frac{a}{m}[/tex]
b)[tex]lim=\frac{\sqrt[m]{1+ax}-\sqrt[n]{1+bx}}{x}=\frac{\sqrt[m]{1+ax}-1+1-\sqrt[n]{1+bx}}{x}=\frac{ax}{x(1+\sqrt[m]{ax+1}+...+\sqrt[m]{ax+1}^{m-1})}-\frac{bx}{x(1+\sqrt[n]{bx+1}+...+\sqrt[n]{bx+1}^{n-1})}=\frac{a}{m}-\frac{b}{n}[/tex]
lim x-->0 ([tex]\frac{\sqrt[m]{1+ax}.\sqrt[n]{1+bx}-1}{x}[/tex])
lim x-->0 ([tex]\frac{\sqrt[m]{1+ax}-\sqrt[n]{1+bx}}{x}[/tex]